Karakter Dan Kepribadian Individu Dalam Melakukan Kolaborasi Interprofessional - Agustini Liviana Dwi Rahmawati (Indonesian Journal of Nursing Scientific, 2022)
Background: The high level of effectiveness in healing patients undergoing treatment at the hospital can be influenced by how cooperation is established between medical personnel. The establishment of this collaboration is due to a collaboration carried out by doctors, nurses, and other medical personnel. In collaborating, it takes the existence of a relationship that is a key interprofessional component in determining patient care. The collaboration carried out by medical personnel can be optimal if each individual has the same autonomy and a good mentality so that they are able to carry out this collaboration in a professional manner. Purpose: To find out how the character and personality of individuals in carrying out interprofessional collaboration in the treatment ward at the Hospital. Method: The author uses several databases to search literature with the same keywords. The author uses the prism method to describe the flow from searching for literature to obtaining the literature used by the author as a search result. Also, the author also uses the synthesis table to explain the results of this scientific paper. Results: Collaboration carried out between health professional teams has factors that can be seen to determine the optimal level used. Collaboration carried out by nurses-doctors must have a strong relationship so that collaboration can be optimally established. Conclusion: Interprofessional collaboration can be done in patient care because it can effectively impact patients undergoing treatment. Collaboration that exists is influenced by the relationship that exists between health professionals where there are factors that influence the relationship, namely emotions, communication factors, mentality, character, and personality of the individual.